2023
DOI: 10.1109/access.2023.3327918
|View full text |Cite
|
Sign up to set email alerts
|

Safety Testing of Automated Driving Systems: A Literature Review

Fauzia Khan,
Mariana Falco,
Hina Anwar
et al.

Abstract: The advancement of automation in safety-critical systems has opened the door to newer opportunities in several fields. However, the increasing complexity has led to more risks and the need for better safety assessment. Safety testing of Automated Driving Systems (ADS) became an important research topic due to the potential benefits of reducing traffic congestion, time, and even accidents; however, safety remains an ongoing issue. We analyzed the existing literature from the past twenty-five years by performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Practically, the results demonstrated that models trained at specific speeds exhibit decreased performance when tested at novel speeds. This poses a challenge for the real-life testing of end-to-end ADS because deploying models at human-like speeds increases risks [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Practically, the results demonstrated that models trained at specific speeds exhibit decreased performance when tested at novel speeds. This poses a challenge for the real-life testing of end-to-end ADS because deploying models at human-like speeds increases risks [ 36 ].…”
Section: Discussionmentioning
confidence: 99%